Pandan Wangi rice as reference food and the use of 25 g portion in glycemic index test - Didah Nur Faridah; Puspo Edi Giriwono; Ratna Sari Listyaningrum; Masayu Nur Ulfa (Universitas Ahmad Dahlan, 2022)
The notion of the Glycemic Index (GI) can be utilized to aid in the choosing of foods for a healthy diet, leading to low GI claims that have been commonly found in various food products. The convenience of the test subject could affect GI results, such as the type of reference food and how much of it to be consumed. Therefore, the goals of this research were to see if white rice (Pandan Wangi) could be used as a reference food and to compare GI result obtained from a different portion of available carbohydrate. The recruited subjects ranged in age from 21-36 years old with BMI of 18.5-24.9 kg/m2). Glucose measurement and sample testing (white rice and cookies) were conducted in the experiment. Overnight fasting was required of volunteers, and blood samples were obtained using One Touch Ultra Lifescan. There were seven points of blood sampling with triplication of glucose testing GI values were calculated with Incremental Area Under Curves (IAUC). The result means of GI were 74±16 (white rice), 60±24 (wheat cookies), 38±14 (NS-cookies), and 39±16 (HMT-cookies). The correlation between IAUC glucose and rice was significant with r=0.834 (n=10, p<0,01). GI of white rice based on 25g available carbohydrates (AVCHO) was significantly different from GI based on 50g AVHCO (n=10, p<0.05). Pandan Wangi white rice can be used to substitute glucose or white bread in GI tests with a conversion factor of 0.74. It needed further study regarding the use of 25 g AVCHO as the basic portion in GI test.